Longitudinal outcomes of final kissing balloon inflation in coronary bifurcation lesions treated with a single stent - He, Lefan; Robb, John F.; Martinez-Camblor, Pablo; Andrus, Bruce W.; Greene, Lily J.; Gongal, Prajesh; Reddy, Dhruthi S.; DeVries, James T. (Frontiers in Cardiovascular Medicine, 2023)
Background: Final kissing balloon inflation (FKBI) is a percutaneous coronary intervention (PCI) technique that is considered mandatory to improve outcomes in two-stent strategies, but its use in single-stent bifurcation PCI remains controversial.In this retrospective cohort study, we identified patients with coronary bifurcation lesions treated with one stent from January 2012 to March 2021 at a single academic medical center. Incidence rates per 1,000 patient-years (IR1000) were calculated for the outcomes of allcause mortality, myocardial infarction (MI), stent thrombosis (ST), target lesion revascularization (TLR), coronary artery bypass graft (CABG), and cardiac readmission between patients who received FKBI and those who did not over a median follow up of 2.3 years. Studied outcomes were adjusted for all baseline clinical and procedural characteristics.Results: This study included 893 consecutive patients of which 256 received FKBI and 637 did not. The IR1000 for MI were 51.1 and 27.6 for patients who received FKBI and patients who did not, respectively (adjusted HR = 2.44, p = 0.001). The IR1000 for death were 31.2 and 52.3 for patients who received FKBI and patients who did not, respectively (adjusted HR = 0.68, p = 0.141). The incidence rates of ST, TLR, CABG, and cardiac readmissions were similar between patients who received FKBI and those who did not.Conclusions: These results suggest that performing FKBI in a one-stent technique was associated with higher rates of myocardial infarction, particularly in the first 6 months, and no difference in death, ST, TLR, CABG, and cardiac readmission rates.